Step-by-step explanation:
y=mx+c
Take c from both sides:
y-c = mx
Divide both sides by m:
(y-c) / m =x
Now swap sides to make it prettier:
x = (y-c) / m
I’m pretty sure the answer is A
Answer:
1867
Step-by-step explanation:
What do you need it for?
Answer:
see explanation
Step-by-step explanation:
Given
2cosΘ -
= 0 ( add
to both sides )
2cosΘ =
( divide both sides by 2 )
cosΘ = ![\frac{\sqrt{2} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B2%7D%20%7D%7B2%7D)
Since cosΘ > 0 then Θ is in first and fourth quadrants, hence
Θ =
(
) = ![\frac{\pi }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cpi%20%7D%7B4%7D)
OR
Θ = 2π -
= ![\frac{7\pi }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B7%5Cpi%20%7D%7B4%7D)
solutions are Θ =
, ![\frac{7\pi }{4}](https://tex.z-dn.net/?f=%5Cfrac%7B7%5Cpi%20%7D%7B4%7D)